Glucose-responsive silk fibroin microneedles for transdermal delivery of insulin - Tan, Guohongfang (2023)
Microneedles (MNs) have attracted great interest as a drug delivery alternative to subcutaneous injections for treating diabetes mellitus. We report MNs prepared from polylysine-modified cationized silk fibroin (SF) for responsive transdermal insulin delivery. Scanning electron microscopy analysis of MNsâ appearance and morphology revealed that the MNs were well arranged and formed an array with 0.5 mm pitch, and the length of single MNs is approximately 430 Î¼m. The average breaking force of an MN is above 1.25 N, which guarantees that it can pierce the skin quickly and reach the dermis. Cationized SF MNs are pH-responsive. MNs dissolution rate increases as pH decreases and the rate of insulin release are accelerated. The swelling rate reached 223% at pH = 4, while only 172% at pH = 9. After adding glucose oxidase, cationized SF MNs are glucose-responsive. As the glucose concentration increases, the pH inside the MNs decreases, the MNsâ pore size increases, and the insulin release rate accelerates. In vivo experiments demonstrated that in normal Sprague Dawley (SD) rats, the amount of insulin released within the SF MNs was significantly smaller than that in diabetic rats. Before feeding, the blood glucose (BG) of diabetic rats in the injection group decreased rapidly to 6.9 mmol/L, and the diabetic rats in the patch group gradually reduced to 11.7 mmol/L. After feeding, the BG of diabetic rats in the injection group increased rapidly to 33.1 mmol/L and decreased slowly, while the diabetic rats in the patch group increased first to 21.7 mmol/L and then decreased to 15.3 mmol/L at 6 h. This demonstrated that the insulin inside the microneedle was released as the blood glucose concentration increased. Cationized SF MNs are expected to replace subcutaneous injections of insulin as a new modality for diabetes treatment.